INTEGRATING INSTITUTIONAL ARCHITECTURE AND DIGITAL MONITORING IN THE GOVERNANCE OF YOUTH WORK IN HIGHER EDUCATION: A SYSTEMS-BASED FRAMEWORK AND MATURITY MODEL FOR UZBEKISTAN - Ziyoda A. Aripova,; Zafarova Sariya Rustamovna, (TADQIQOTLAR, 2026)
Abstract:  Uzbekistan’s  higher  education  system  has  expanded  from  roughly nine per cent gross enrolment in 2017 to about forty-two per cent in 2025, and the Uzbekistan-2030 Strategy sets a target of at least fifty per cent. This rapid growth has pushed the management of youth work — the organised support of students’ social, civic,  professional  and  psychological  development  —  to  the  centre  of  institutional agendas,  yet  the governance of this domain  remains uneven and  weakly  theorised. Purpose. The study develops and argues for an integrated framework that unifies three threads usually treated separately in the literature: the systems-theoretic understanding of youth work, the institutional architecture of universities, and the digital monitoring of  student  engagement.  Methods.  A  qualitative,  conceptual-analytical  design combined  a  structured  review  of  national  and  international  sources,  comparative analysis  of  foreign  practice,  content  analysis  of  regulatory  documents,  and  semi-structured expert interviews with managers, educators and psychologists at three higher education institutions in Tashkent, supported by direct observation of extracurricular activity.  Results.  Three  reinforcing  directions  of  development  were  identified  — digital  management  technologies,  socio-psychological  approaches,  and  integrated monitoring  —  alongside  persistent  fragmentation,  formalistic  evaluation  and  a shortage of specialised personnel. Building on these findings, the paper proposes the Integrated Digital–Institutional Governance (IDIG) framework and an accompanying five-level  Youth-Work  Governance  Maturity  Model.  Conclusions.  Effectiveness depends less on adding activities than on connecting them: a shared governance core, a  common  data  layer  and  adaptive  feedback  move  institutions  from  fragmented, reactive  practice  toward  data-informed,  anticipatory  governance.  The  framework offers a transferable diagnostic and design tool for systems undergoing comparable expansion.